Effects of different resin content and particle sizes on properties of three layered particleboard using oil palm frond / Siti Noorbaini Sarmin and Jamaludin Kasim - Sarmin, Siti Noorbaini; Kasim, Jamaludin (Research Management Institute (RMI), 2012)
The objective of this study was to examine the properties of three layered particleboard from oil palm frond (OPF) with different ratio resin contain and particle sizes within face/back and core. Four different ratio of resin contain; 12:10:12, 12:8:12, 10:10:10 and 10:8:10 were used with particle size for core; 2mm and face/back; 1mm. Urea Formaldehyde (UF) was used as a binder with addition of wax and without wax. The target density was 500kg/m3. The properties of bending strength, internal bonding (IB), thickness swelling (TS) and water absorption (WA) were evaluated base on JIS A-5908 standard. From the result, it shown that modulus of rupture and modulus of elasticity were perform better with particleboard using ratio 12:8:12 bonded with UF without wax and meet the standard. The internal bond strength was parallel with bending strength except for board using 12:10:12 ratio bonded using UF with addition of wax. Samples using resin contain with ratio 12:8:12 had the lowest thickness swell and water absorption but did not meet the above standard. The thickness swelling and water absorption rate were reduced in samples prepared with addition of wax. The ratio of resin contain within the layered affected the properties of particleboard manufactured from oil palm frond. Based on the findings of this study, oil palm frond has the potential to be used to manufacture particleboard, and further study is required to improve its dimensional stability.